Current affairs journalism (North Ryde, NSW. : Australian Film Television & Radio School, 1986)
Mike Minehan interviewed Jonathan Holmes, executive producer of Four Corners on important aspects of the television interview and the methods of conducting an interesting, thorough interview.
Interviewer : Mike Minehan
Keywords: Interviewing in television; Talk shows